Evaluation of Anticancer Activity of Satureja montana Supercritical and Spray-Dried Extracts on Ehrlich’s Ascites Carcinoma Bearing Mice - Jelena Vladić; Tatjana Ćebović; Senka Vidović; Stela Jokić (Plants, 2020)
Satureja montana herbal species belongs to aromatic medicinal plants with a significant place in traditional medicine. However, products produced with conventional procedures do not meet the requirements of the modern market which include environmentally-safe processes that provide quality, safe, and standardized products. In this study, the antiproliferative activity of S. montana extracts obtained by supercritical carbon dioxide and solid–liquid extraction followed by spray drying was investigated using the in vivo model of Ehrlich ascites carcinoma (EAC) in mice. The impact of two concentrations of extracts on the growth of tumor and the redox status of malignant cells was monitored. It was determined that the extracts induced oxidative stress in the malignant cells which was confirmed by the changes in activity of biochemical indicators of oxidative stress. The posttreatment was not an efficient approach, while the extracts applied as pretreatment and treatment resulted in an increase in the xanthine oxidase (XOD) activity, a decrease in catalase (CAT) activity, and an increase in the intensity of lipid peroxidation (LPx). Furthermore, a decrease in the values of reduced glutathione (GSH) and an increase in glutathione reductase (GR) and glutathione peroxidase (GSHPx) in EAC cells were recorded.